Pronunciation Difficulties in English Learning: A Contrastive Analysis of MTs Students' Performance in East Kalimantan - Rostanti Toba; Anis Komariah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This study investigates the pronunciation difficulties encountered by MTs students in East Kalimantan when learning English as a foreign language. Using a comparative qualitative research method combining contrastive analysis between regional languages (as the first language or L1) and English (as a foreign language), this research examines the types of mispronunciations and underlying causal factors affecting 40 students from MTs Negeri 3 Paser and MTs Negeri 1 Penajam Paser Utara. Data collection involved students’ pronunciation recordings, in-depth interviews, and classroom observations. Findings reveal nine primary categories of pronunciation errors: (1) /gh/ endings pronounced as /f/, (2) silent /gh/ in word-medial positions, (3) silent /l/, (4) word-final /-d/, (5) word-initial /t/, (6) word-medial /ʒ/, (7) /ʃ/ substitution, (8) /θ/ substitution, and (9) word-final /-t/. Three main causal factors emerged: regional accent interference, phonological differences between the first language or L1/L2 (second language) and English, and unsupportive language environments. The study contributes to understanding multilingual students' English pronunciation challenges in Indonesian contexts and provides pedagogical implications for EFL (English as a Foreign Language) instruction.